A scalable fast forwarding approach for IP networks. (29th September 2008) - Xiong, Ke; Qiu, Zheng-Ding; Zhang, Hong-Ke; Li, Chung-Sheng; , Han-Chieh Chao
In the internet era, how to optimise cost and performance of routers is the objective of traffic engineering especially for real time services. In this paper, we aim at excogitating a new approach to achieve fast switch, scalability, simplicity and enhancement of the IP Network QoS performances. The new forwarding approach To Next-hop Output Port Sequence Switch (TNPOSS), which can work on the existing routing protocols, achieve fast switch and execute like Explicit Route by setting up a connection-oriented Output-port Sequence Path (OSP). Our simulation results show that TNPOSS can provide shorter end-to-end delay and more throughputs than MPLS.